46.5k views
1 vote
Item 7
Find the sum.
3(2−0.9h)+(−1.3h−4) =

User Steve Pugh
by
6.5k points

2 Answers

3 votes

3.(2 - 0,9h) + (-1,3h - 4)

3.2 - 3.0,9h - 1,3h - 4

6 - 2,7h - 1,3h - 4

2 - 4h

User JanLeeYu
by
5.5k points
0 votes

Answer:

= 2(1 - 2h)

Explanation:

Given that:

=3(2−0.9h)+(−1.3h−4)

Simplifying:

=(6 - 2.7h) + (-1.3h - 4)

Removing brackets

=6 - 2.7h -1.3h - 4

Adding like terms (h terms and constants)

= 2 - 4h

We can take 2 common as:

= 2(1 - 2h) Required sum

I hope it will help you!

User Thebitguru
by
6.0k points